The implementation by Tanzania of orders of the African Court on Human and Peoples’ Rights requiring constitutional and legislative reform - Prof Viljoen, Frans (University of Pretoria, 2024)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2024.